Theoretical aspects of electron-transfer processes mediated by metal macrocyclic molecules - Zagal-Moya, J; Zagal-Moya, J (Elsevier, 2025)
This chapter reviews the theoretical foundations of electron transfer with emphasis on metal MN4 macrocyclic systems, which serve as discrete platforms for studying electrochemical processes. The fundamentals of Marcus’ theory and its extensions are introduced to describe homogeneous and heterogeneous electron-transfer mechanisms. Special attention is given to MN4 cores confined on solid electrodes, where multielectron inner-sphere pathways mediate the oxygen reduction reaction. Density functional theory approaches are highlighted for their ability to describe electronic, structural, and energetic features of redox species and adsorbed intermediates. Reactivity descriptors, such as O2-adsorption energy, are discussed in correlation with experimental properties, such as M(III)/M(II) redox potentials, underlining their value for the rational design of advanced catalytic materials, including doped M–N–C systems. Finally, the chapter addresses the limitations imposed by scaling relationships in multielectron processes and suggests current molecular design strategies aimed at overcoming these barriers. © 2026 Elsevier Inc. All rights reserved.